Screening tomato genotypes for resistance against collar rot disease caused by Alternaria solani Sorauer - Yerasu, Suresh Reddy; Murugan, Loganathan; HC, Prasanna; Singh, Arpita (Vegetable Science, 2019)
Alternaria solani is a soil borne pathogen causing heavy losses to tomato (Solanum lycopersicum L) crop worldwide. It causes early blight symptoms on foliage, collar rot symptom at basal stem region of seedlings, stem lesions on stem of adult plants and fruit rot symptoms on fruits. In comparison to early blight, collar rot screening and differentiating genotype into different resistance classes isrelatively easy. To identify collar rot resistant genotypes thirty tomato accessions of the ICAR-Indian Institute of Vegetable Research, Varanasi, gene bank was screened by inoculating the pathogen under screen house conditions. Three genotypes including two tomato wild species LA 2325(S. neorickii) and WIR 3928 (yellow fruited wild species), and an advanced breeding line H-88-78-1 showed immune reaction to collar rot with zero mean disease severity index. The identified lines are being used as a source of resistance to A. solani to develop disease resistant cultivars.